Response of Swamp Rice Elite lines to Submergence in Early Phase of Tiller Formation - Sumardi Sumardi; Mohammad Chozin; Rafi Anwar (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The development of swamp rice varieties tolerant to submergence is an important step in reducing the impact of floods that often occur in swamplands. The objective of this study was to evaluate the response of eight genotypes of swamp rice in the early stages of tillering to submergence stress. The experiment was carried out using a completely randomized design with three replications. Pots filled with swamp soil were used as the growing media and a tarpaulin pond was used to submerge the plants. The swamp rice lines evaluated were UBPR 2, UBPR 6, UBPR 7, UBPR 8, UBPR 10, and UBPR 11 with Inpari 30 variety as the resistance check variety and Batang Piaman variety as the susceptible check variety. The results showed that the genotypes had varying degrees of growth recovery following the exposure of 10 days of submergence stress. UBPR 7, UBPR 8, UBPR 10, and UBPR 11 tend to recover faster than other genotypes, classified as tolerant based on plant height, and the number of leaves and leaf greenness are moderately tolerant